Sinovac Vaccine According to the Fatwa of the Indonesian Ulema Council Number 2 of 2021 Sharia Maqāṣid Perspective - Kara, Siti Aisyah; Indah, Nur (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2022)
This study aims to analyze views on the use of the Sinovac vaccine based on the Fatwa of the Indonesian Ulema Council Number 2 of 2021 with the perspective approach of Maqasid Al-Syari'ah. Maqasid Al-Shari'ah is a conceptual framework in Islamic law that emphasizes the maintenance of fundamental goals, including religion, soul, reason, heredity, and property. In the context of the COVID-19 pandemic, vaccination has become a global debate, including the Sinovac vaccine. Through document analysis, the fatwa was analyzed in relation to the principles of Maqasid Al-Shari'ah in order to understand the extent to which the view supports the use of the Sinovac vaccine. In answering these problems and descriptive data analysis, the author uses a juridical normative approach. This research is classified as library research with a type of qualitative description research, where data is collected by quoting, adapting, and analyzing content (content analysis) of literature that is representative and has relevance to the problem discussed, then reviews and concludes it. Researchers found that vaccination has goals including stimulating the immune system, reducing the risk of transmission, reducing the severe impact of the virus and achieving herd immunity. In determining the halality of the COVID-19 vaccine, using the opinions of scholars who emphasize that treatment for illness and guarding against outbreaks is mandatory. Then use the concept of istihalah. And finally, the conclusion of jurisprudence related to vaccines is based on general rules of jurisprudence decision-making by authorities and experts in their fields. Maqasid al-Sharia against MUI fatwa number 2 of 2021, is the implementation of preserving the soul (hifz al-nafs). Vaccination efforts are part of achieving benefits by rejecting harm. Maqasid al-Sharia in this case is a special purpose where the desired ways of shari' protect the soul / self (Hifz al-nafs) from contracting covid-19. The fatwa also places emphasis on health care, life protection, and public benefit. Despite questions about the efficacy and halality of vaccines, the fatwa provides a foothold that in emergency situations, safeguarding public health and safety is a key principle. This research provides insight into how the interpretation of Maqasid Al-Shari'ah in fatwas can help formulate guidelines in dealing with contemporary issues such as the use of vaccines in a public health context